2019
DOI: 10.3390/su11102787
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Perennial and Annual Phaseolus Seed Nutrient Concentrations

Abstract: Long-term agricultural sustainability is dependent in part on our capacity to provide productive, nutritious crops that minimize the negative impacts of agriculture on the landscape. Perennial grains within an agroforestry context offers one solution: These plants produce large root systems that reduce soil erosion and simultaneously have the potential to produce nutrients to combat malnutrition. However, nutrient compositions of wild, perennial, herbaceous species, such as those related to the common bean (Ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Additionally, there are other morphological traits modified during domestication, such as seed or plant tissue composition that are far less studied, especially in legumes. Different accumulation of nutrients, such as microelements, was recently shown in comparative analysis of wild and cultivated Phaseolus species (Schier et al, 2019). A recent study showed decrease carotenoids in crops compared with respective progenitors (Fernández‐Marín et al, 2014).…”
Section: How To Effectively Use the Diversity Of Cwrs?mentioning
confidence: 92%
“…Additionally, there are other morphological traits modified during domestication, such as seed or plant tissue composition that are far less studied, especially in legumes. Different accumulation of nutrients, such as microelements, was recently shown in comparative analysis of wild and cultivated Phaseolus species (Schier et al, 2019). A recent study showed decrease carotenoids in crops compared with respective progenitors (Fernández‐Marín et al, 2014).…”
Section: How To Effectively Use the Diversity Of Cwrs?mentioning
confidence: 92%
“…Of course, many annual staple crops are also nutritionally important and constitute an essential part of gastronomic cultures. Moreover, specific annual crops may be more nutritionally dense than their perennial counterparts in some cases, as documented in one study of micronutrients of annual and perennial Phaseolus species (Schier et al, 2019). We do not advocate for the outright replacement of annual crops, but rather, for a reemphasis on perennial staple crops in those geographic and cultural contexts where exotic annual staple crops have been privileged by development agencies and colonial sensibilities over culturally established, Indigenous, perennial staple crops (Brandt et al, 1997;Chifamba, 2011;Rogé et al, 2016).…”
Section: Agronomy Of and Nutrition From Perennial Staplesmentioning
confidence: 98%
“…Efforts to this end are actively taking place through breeding projects to either perennialize herbaceous annual staple crops, or domesticate wild perennial grasses for food production (e.g., Kernza-Thinopyrum intermedium [Host] Barkworth & D.R.Dewey, a domesticated version of a wild perennial wheatgrass; Glover et al, 2012). For these breeding projects, and for a few shorter-lived perennial staple crops that have congeneric annual crops (such as beans), agronomic and environmental outcomes can be directly compared to the equivalent annual species (Vico and Brunsell, 2018;Schier et al, 2019). But scientific analyses on a global food system scale are lacking for already existing and nutritionally important perennial staple crops.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of inorganic fertilizers is a cost-effective, simple, and quick method of agronomic biofortification, it has several drawbacks. The main downside is related to the misuse of inorganic fertilizers, which has negative environmental consequences such as water pollution, algal bloom, and biodiversity loss in various natural systems (Zhang et al, 2019;Schier et al, 2019;Jewell et al, 2020). Moreover, these are expensive, if considered for bulk application to soil, and labor-intensive to apply, which may further impoverish farmers with small holdings.…”
Section: Advances In Fertilizer Forms Revive Agronomic Biofortificationmentioning
confidence: 99%